2019
DOI: 10.3390/fib7090080
|View full text |Cite
|
Sign up to set email alerts
|

Plant Fibers and Phenolics: A Review on Their Synthesis, Analysis and Combined Use for Biomaterials with New Properties

Abstract: Devising environmental-friendly processes in biotechnology is a priority in the current economic scenario. We are witnessing a constant and steady push towards finding sustainable solutions to societal challenges by promoting innovation-driven activities minimizing the environmental impact and valorizing natural resources. In bioeconomy, plants are among the most important renewable sources of both fibers (woody and cellulosic) and phytochemicals, which find applications in many industrial sectors, spanning fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…Since the only difference between 43 and 44 is the absence and presence of the acetoxy group, it can be assumed that acetylation of 43 decreased biological activities. Interestingly, 43 and 44 were remarkably active against Chinese hamster fibroblasts (V79), unlike stypodiol (45), which showed little effect on normal cells [181]. The neurotoxicity of meroditerpenes from S. flabelliforme was also demonstrated by Sabry and co-workers [183].…”
Section: Terpenophenolicsmentioning
confidence: 88%
See 3 more Smart Citations
“…Since the only difference between 43 and 44 is the absence and presence of the acetoxy group, it can be assumed that acetylation of 43 decreased biological activities. Interestingly, 43 and 44 were remarkably active against Chinese hamster fibroblasts (V79), unlike stypodiol (45), which showed little effect on normal cells [181]. The neurotoxicity of meroditerpenes from S. flabelliforme was also demonstrated by Sabry and co-workers [183].…”
Section: Terpenophenolicsmentioning
confidence: 88%
“…The highest activity of almost 100% inhibition of cell proliferation was observed against human neuroblastoma cells (SH-SY5Y) for all compounds. Even though the authors did not provide the exact IC 50 values, they can be clearly seen from the reported graphical representations as 6.25-12.5, <12.5 and 12.5-25 µM for epitaondiol (43), epitaondiol monoacetate (44) and stypodiol (45), respectively. Since the only difference between 43 and 44 is the absence and presence of the acetoxy group, it can be assumed that acetylation of 43 decreased biological activities.…”
Section: Terpenophenolicsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this review, various applications of plants used as bioresources are discussed, providing valuable raw materials used as additives in polymeric matrices, such as lignocellulosic fibers [69] and nano-cellulose [70], as well as plant extracts containing bioactive phenolic compounds [42] used in the pharmaceutical and cosmetic industries [71]. The increasing environmental concerns draw attention on their use as active compounds, instead of synthetic ones.…”
Section: Lignocellulosic Materials and Plant Extracts In Polymeric Comentioning
confidence: 99%